Analisis Faktor Penyebab Rendahnya Hasil Belajar Siswa pada Pembelajaran IPA Kelas IV SD Negeri 105358 Sekip Lubuk Pakam - Amanda; Umar Darwis (Melati Institute, 2023)
This research aims to find out about the factors that cause low student learning outcomes in class IV science learning at SD Negeri 105358 Sekip Lubuk Pakam. This research is to make it easier for teachers to understand what factors cause low student learning outcomes at SD Negeri 105358 Sekip Lubuk Pakam. This type of research is qualitative descriptive research. The subjects of this research were 16 class IVB students who were identified as having low daily test scores. Data collection was carried out using questionnaires, interviews and documentation. According to Miles and Huberman, data analysis includes: 1) Data Display (Data Presentation), 2) Data Reduction (Data Reduction), 3) Verification (Conclusion Drawing). The results of the research show that the factors that cause low learning outcomes in class IVB students at SD Negeri 105358 Sekip Lubuk Pakam are internal factors (coming from oneself), interest factors, talent factors, and learning concentration factors. Based on the results of the questionnaire given to students: 1) Health Factor with a percentage of 100% which is classified as very high, 2) Interest Factor with a percentage of 25% which is classified as low, 3) Talent Factor with a percentage of 25% which is classified as low, 4) Learning Concentration Factor with a percentage of 29% which is classified as low, 5) Family Factors with a percentage of 52% which is classified as high, 6) Community Factors with a percentage of 56% which is classified as high, 7) School Factors with a percentage of 44% which is classified as medium.